Radiochemistry and Preclinical PET Imaging of Ga-Desferrioxamine Radiotracers Targeting Prostate-Specific Membrane Antigen - Eleni Gourni PhD; Luigi Del Pozzo BSc; Mark Bartholomä PhD; Yvonne Kiefer BSc; Philipp T. Meyer MD, PhD; Helmut R. Maecke PhD; Jason P. Holland D.Phil (Molecular Imaging, 2017)
Radiotracers incorporating the urea-based Glu-NH-C(O)-NH-Lys group have gained prominence due to their role in targeting prostate-specific membrane antigen (PSMA)—a clinical biomarker of prostate cancer. Here, the synthesis, radiolabeling, and in vitro and in vivo characterization of two 68 Ga-radiolabeled Glu-NH-C(O)-NH-Lys radiotracers conjugated to the desferrioxamine B (DFO) chelate were evaluated. Two linker groups based on amide bond and thiourea coupling chemistries were employed to develop 68 Ga-DFO-Nsucc-PSMA ( 68 Ga-4) and 68 Ga-DFO- p NCS-Bn-PSMA ( 68 Ga-7), respectively. Radiosynthesis proceeded quantitatively at room temperature with high radiochemical yields, chemical/radiochemical purities, and specific activities. Pharmacokinetic profiles of 68 Ga-4 and 68 Ga-7 were assessed using positron-emission tomography (PET) in mice bearing subcutaneous LNCaP tumors. Data were compared to the current clinical benchmark radiotracer 68 Ga-HBED-CC-PSMA ( 68 Ga-1) (HBED = N,N′-Bis(2-hydroxy-5-(ethylene-beta-carboxy)benzyl)ethylenediamine N,N′-diacetic acid). Results indicated that the target binding affinity, protein association, blood pool and background organ clearance properties, and uptake in PSMA-positive lesions are strongly dependent on the nature of the chelate, the linker, and the spacer groups. Protein dissociation constants ( K d values) were found to be predictive of pharmacokinetics in vivo. Compared to 68 Ga-1, 68 Ga-4 and 68 Ga-7 resulted in decreased tumor uptake but enhanced blood pool clearance and reduced residence time in the kidney. The study highlights the importance of maximizing protein binding affinity during radiotracer optimization.